Analysis of factors influencing mothers’ ability to care for premature infants at home based on health promotion model theory - Rinik Eko Kapti; Nurona Azizah; Chui Ping Lei; Yuni Sufyanti Arief; Mira Triharini; Ari Damayanti Wahyuningrum (Universitas Airlangga, 2026)
Introduction: Premature infants need adequate care both during hospitalization and at home. However, mothers have relatively low capabilities in caring for premature infants. Objective: This study aimed to determine the factors influencing mothers' ability to care for premature infants at home. Methods: This study used a descriptive-analytic design with a cross-sectional approach and was conducted in the Greater Malang area (Malang Regency, Malang City, and Batu City). A total of 188 mothers were obtained using a convenience sampling technique. Inferential analysis was performed using Partial Least Squares (PLS) structural equation modelling. Results: Infant factors, particularly infant characteristics and birth weight, were the most significant factors influencing support from partners, peers, and health workers. Support was identified as the strongest factor associated with maternal commitment, which consisted of strategic commitment and caregiving action. Commitment subsequently was the most significant factor that influenced mothers' ability to care for premature infants at home, which consisted of nutrition fulfillment, infection prevention, recognition of danger signs, and stimulating development, with an R-square value of .582. The model explained 58.2% of the variance in maternal caregiving ability, indicating moderate to strong predictive power. Conclusion: Mothers caring for premature infants require strengthening in cognitive and affective aspects. Healthcare workers should consider infant and maternal factors when developing interventions to improve mothers' ability to care for premature infants at home. Keywords: ability; health promotion model; mother; premature infants